Kedudukan Hukum Klausula “Penyerahan dan Pengalihan Jaminan” Pada Akta Pemberian Jaminan dan Kuasa Pada Bank Swasta di Medan - Jesline Arsjad; Sutiarnoto; Suhaidi Suhaidi (CV Rewang Rencang, 2025)
Banks as financial institutions play an important role in channeling credit to the public with collateral to guarantee debt repayment. In practice, a private bank in Medan uses a Guarantee and Power of Attorney (PJDK) deed in take over credit schemes to bind certificated land rights as collateral. Juridical empirical research shows that using PJDK deeds deviates from the principles of Law No. 4 of 1996 on Mortgage Rights, which establishes mortgage rights as the sole security institution for registered land rights. Consequently, binding through PJDK does not fulfill the principles of legal certainty and creates risks of legal uncertainty for debtors and weak executorial power for creditors over collateral objects bound through PJDK deeds.